Associations of Serum Resistin With the Severity and Prognosis in Patients With Community-Acquired Pneumonia - Feng, Chun-Mei; Cheng, Jia-Yi; Xu, Zheng; Liu, Hong-Yan; Xu, De-Xiang; Fu, Lin; Zhao, Hui (Frontiers in Immunology, 2021)
Background: Resistin is an endogenous ligand of toll-like receptor 4 that activates several inflammatory signals. But, the physiology function of resistin in community-acquired pneumonia (CAP) remains unknown. The goal of this research was to explore the associations between serum resistin with the severity and prognosis in CAP patients through a retrospective cohort study. Methods: All 212 CAP patients and 106 healthy cases were enrolled. Demographic characteristics were extracted. Serum resistin was determined via enzyme-linked immunosorbent assay. The prognosis was tracked in CAP patients. Results: Serum resistin on admission was raised in CAP patients compared with control cases. The level of resistin was gradually increased in parallel with CAP severity scores in CAP patients. Pearson and Spearman analysis analysis revealed that serum resistin was positively correlated with CAP severity scores, white blood cells, urea nitrogen, creatinine and inflammatory cytokines among CAP patients. There were negative relationships between resistin with hematocrit and albumin in CAP patients. Besides, linear and logistical regression analysis further indicated that serum resistin on admission was positively associated with CAP severity scores among CAP patients. Follow-up research revealed that serum resistin elevation on admission prolonged hospital stay in CAP patients. Conclusion: Serum resistin on admission is positively correlated with the severity and hospital stay in CAP patients, indicating that resistin may involve in the physiological process of CAP. Serum resistin may be a potential biomarker in the diagnosis and prognosis for CAP.